3,5-Bis(4-methoxyphenyl)-4,5-dihydroisoxazole - S. Samshuddin; Ray J. Butcher; Mehmet Akkurt; B. Narayana; H. S. Yathirajan (Acta Crystallographica Section E, 2011)
In the title compound, C17H17NO3, the five-membered isoxazoline ring adopts an envelope conformation with the chiral C atom at the flap position and 0.133 (2) Å out of the mean plane formed by the other four atoms. The two benzene rings form dihedral angles of 6.05 (5) and 81.52 (5)° with the C—C—N—O plane of the isoxazoline ring. The crystal structure is stabilized by weak C—H...O hydrogen bonds and C—H...π interactions.